Comparative Environmental Policy in Sustainable Development: A Case Study of Indonesia and Malaysia - Ramadhani, Asri; Sami AR (Jurnal Abdimas Peradaban, 2022)
This literature review explores the comparative environmental policies of Indonesia and Malaysia within the context of sustainable development. The study aims to identify the key similarities and differences in the policy frameworks of both countries, particularly in addressing environmental challenges while promoting economic growth. By examining existing literature, this review highlights the historical evolution, current strategies, and effectiveness of environmental policies in both nations. The analysis reveals that while Indonesia and Malaysia share common goals of sustainability, their approaches differ significantly in implementation and regulatory frameworks. Indonesia's policy focus is more aligned with community-based environmental management, whereas Malaysia emphasizes top-down governmental intervention. The review also identifies gaps in the current literature, particularly in the areas of policy enforcement and the role of international collaboration. The findings suggest the need for a more integrated approach to environmental policy-making in both countries to enhance sustainable development outcomes. Recommendations for future research include a deeper exploration of cross-border environmental initiatives and the impact of policy harmonization in Southeast Asia.